(In)constitucionalidade da Lei 13954/2019 e o direito do militar temporário: uma análise frente aos princípios da igualdade, dignidade da pessoa humana e a proibição do retrocesso - Pires, Flávio Braga (2023)
This dissertation was presented with the institutional objective of obtain the Master's Degree in Law through the Academic Master's Degree in Law, linked to the Strictu Sensu Postgraduate Program in Law (PPGDireito), University of Passo Fundo (UPF), under the Research Line "Constitutional Jurisdiction and Democracy" and the Concentration Area "New Paradigms of Law". The work assessed whether the changes brought about by Law 13,954/2019, which revoked provisions of the Military Statute (Law 6,880/80), should be considered constitutional or not, in light of the principles constitutional principles of equality, dignity of the human person and the prohibition of regression, which started from the nalysis of constitutional principles, presenting their evolution in relation to the Federal Constitution of Brazil, where facing the new law it was analyzed whether these changes came in social regression or not going against the grain of the Federal Constitution, which has as its generating principle progress and non-retrogression. Using the new law as a basis for the present study, which set out to identify these changes in relation to the Federal Constitution of 1988, where the answer to the question, contained in the title of this research, was reached, where a necessary comparison was made, of the law, in view of the principles of equality, dignity of the human person and prohibition of social regression, where the monographic procedure used was through the inductive scientific method and comparative procedure.